Formula 1 Game Model (Run, Jump, Throw) in Locomotor Activity - Winartiningsih, Anes; Lanos, Muhsana El Cintami; Kristina, Putri Cicilia (Journal of Social Work and Science Education, 2023)
This study aims to examine the role of the Formula 1 game model (Run, Jump, Throw) in locomotor activity. The method in this study uses a qualitative approach to the type of literature study. This study seeks to explore document studies regarding the study of the Formula 1 game model (Run, Jump, Throw) in general and then relate it to the physical learning process in SDN 67 Palembang. Because nature of physical education in elementary schools is an educational process that aims to build the growth and development of students from the physical, intellectual, movement skill, and attitude aspects that are carried out through physical activity or gestures so that they become healthy, intelligent, skilled human beings, and virtuous character so that it can have a good influence on the quality of his life in the future. It is necessary to pay attention to the implementation of physical education in schools because in supporting the growth and development of students it is also determined by the implementation of physical education in schools. Physical education teachers must be more creative in optimizing the developed facilities and infrastructure. If the physical education teacher is creative, then he is able to create something new, or modify an existing one, but present it in the most attractive way possible, so that students will be more interested and enjoy participating in the physical education learning process.